2018
DOI: 10.1007/s10461-018-2088-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV Incidence Disparities Among Young and Older Men Who Have Sex with Men in the United States

Abstract: This study sought to determine why young men who have sex with men (MSM) have higher HIV incidence rates than older MSM in the United States. We developed hypotheses that may explain this disparity. Data came from peer-reviewed studies published during 1996-2016. We compared young and older MSM with respect to behavioral, clinical, psychosocial, and structural factors that promote HIV vulnerability. Compared with older MSM, young MSM were more likely to have HIV-discordant condomless receptive intercourse. You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 113 publications
0
23
0
1
Order By: Relevance
“…Data from the U.S. found that socioeconomic disparities were related to age among MSM, with YMSM having less income, less access and use of health care services compared to their older counterparts [ 30 ]. In addition, socio demographic characteristics, such as race and education, were more strongly associated with HIV infection than individual risk behavior among YMSM [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the U.S. found that socioeconomic disparities were related to age among MSM, with YMSM having less income, less access and use of health care services compared to their older counterparts [ 30 ]. In addition, socio demographic characteristics, such as race and education, were more strongly associated with HIV infection than individual risk behavior among YMSM [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among youth, there are key populations who bear disproportionate burdens of HIV and are the most vulnerable, including young men who have sex with men (MSM), transgender youth, those who inject drugs, and adolescent girls and young women in Africa. Among young men who have sex with men (YMSM) in the United States, psychosocial and structural factors substantially contribute to age-associated HIV incidence disparities, including depression, substance use, STI infections, poverty, decreased health care access and early sexual debut [14]. For adolescent girls and young women (AGYW), many of the same drivers of increased risk for young MSM are also relevant, including poverty, lack of access to school and health care, depression, and gender power imbalances and sexual violence.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, two thirds of diagnosed human immunodeficiency virus (HIV) infections in the United States were attributed to male-to-male sexual contact ( 1 ). The risk for sexual acquisition and transmission of HIV changes through the lifespan ( 2 ); to better guide prevention efforts for gay, bisexual, and other men who have sex with men (MSM * ), CDC analyzed National HIV Surveillance System † (NHSS) data for MSM aged ≥13 years by age group (13–29, 30–49, and ≥50 years) in 50 states and the District of Columbia (DC). During 2008–2016, the annual number of diagnoses of HIV infection increased 3% per year among MSM aged 13–29 years, decreased 4% per year among those aged 30–49 years and was stable for MSM aged ≥50 years.…”
mentioning
confidence: 99%